â€œSEMAMPAIâ€ SEHAT, MANAJERIAL, MANDIRI, DAN PANDAI: KKN-PPM, MUARA ANCALONG, KUTAI TIMUR - Nugroho, Rudy Agung; Sanjaya, Ari Susandy; Ramdan, Iwan Muhammad; Rudianto, Rudianto; Prahastika, Widha (Universitas Muhammadiyah Tapanuli Selatan, 2021)
Community Development Program-learning and community service program or Kuliah kerja nyata-pembelajaran dan pengabdian kepada masyarakat (KKN-PPM) which is a form of community service has been done from July-August 2019 in the Kelinjau Ulu and Kelinjau Ilir village, Muara Ancalong, East Kutai, East Kalimantan. The purpose of the KKN-PPM was to empower the community to be more productive. The theme of the KKN-PPM programÂ was